Molecular determinants for ligand binding at Nav1.4 and Nav1.7 channels: Experimental affinity results analyzed by molecular modeling. (December 2019) - Kong, De-jiang; Wang, Ying; Wang, Han-xun; Wang, Ming-xing; Wang, Jian; Cheng, Mao-sheng
Graphical abstract: Highlights: The first time to explain selectivity from the perspective of the difference between Nav1.7-VSD4 and Nav1.4-VSD4 key amino acids. Com1 and Com2 were selected to prove hypothesis and ideas combining molecular docking, MD simulations and Binding free energy calculations. The causes of different conformations in key amino acids Tyr1386 and Tyr1537 were analyzed. The difference of selectivity between Com1 and Com2 was explained from the structural point of view. Abstract: Here, we focused on exploring the selectivity mechanism against Nav1.7 over Nav1.4 due to different binding modes of two selected inhibitors. By the superposition of Nav1.7 and Nav1.4 proteins, we selected the most homologous chain of Nav1.7 with Nav1.4, defining the active site of Nav1.4-VSD4 based on the aryl sulfonamide binding site of Nav1.7-VSD4. Comparison of the conformations exhibited by Tyr1386 (Nav1.4) and Tyr1537 (Nav1.7) suggested that the steric hindrance caused by Tyr1386 owned primary influence on inhibition selectivity, which was further verified through molecular docking and MD simulation of two representative inhibitors. Our finding would be helpful for discovery of selective Nav1.7 inhibitors over Nav1.4.